Moderate to low knowledge and Positive Attitude towards Medicinal Plants leads to High Consumption of these Plants during Pregnancy - Hosseini , Motahare Sadat; Taheri , Hadiseh; Hosseinzadeh , Ali; Salehi, Majid; Jafarisani , Moslem (Shahroud Journal of Medical Sciences, 2021)
Background: In recent years, the use of medicinal plants in developing countries has increased significantly. However, these plants can cause adverse effects on the mother and fetus. This study aimed to investigate the frequency of use, knowledge, and attitude towards the use of medicinal plants in pregnant women.Methods: This descriptive–analytical study was performed in 2020 on 290 pregnant women referring to Shahroud health center. The first part of the questionnaire included demographic information and the second part included information related to knowledge, attitude, behavior, reasons for using medicinal plants, source of information, etc. The significant level was set at 0.05.Results: 61% of the participants had used the medicinal plants at least once during pregnancy. Most pregnant women had moderate knowledge (50%) and a positive attitude (73.1%) towards the use of medicinal plants. Behavior was significantly associated with knowledge (Pvalue=0.011) and attitude (Pvalue=0.014). The most common problem during pregnancy that caused the use of medicinal plants was heartburn (43.4%) and the main reason for the use of these plants was the availability of them at home or taking from acquaintances (36.6%). 57.2% had obtained their information about medicinal plants from the family.Conclusions: Due to the relatively high frequency of the use of medicinal plants during pregnancy and low knowledge about it, informing and increasing knowledge about medicinal plants during pregnancy is very important.Keywords: Pregnancy, Pregnant women, Medicinal plants, knowledge